Simulation of the Collapse Mechanism of a Minaret under the Effect of Strong Wind - Taha Yasin Altıok; Ali Demir (Firat University Journal of Experimental and Computational Engineering)

(untitled)
In this study, the collapse mechanism of a destroyed minaret under strong wind influence was simulated to understand such structural interactions and identify potential risky regions. Wind profiles were defined according to Eurocode and Turkish Standards and were used in Computational Fluid Dynamics analyses. The pressure and suction stresses obtained with these wind analyses were applied on the minaret’s surface with Abaqus and the nonlinear finite element analyses were performed. As a result of the numerical analyses, displacements, stresses, plastic strains, and damages were obtained and results were comparatively presented. The results obtained with both standards are quite close and top displacements exceed the limit value specified in the Italian Building Code and Eurocode 8. Besides, many mesh elements in the minaret’s transition segment were damaged with tension stresses in nonlinear finite element analyses. Finally, the minaret’s failure behaviour was successfully simulated with the used methods.